2016
DOI: 10.1016/j.bbmt.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Allogeneic Hematopoietic Cell Transplantation in Patients with Myelofibrosis with Prior Exposure to Janus Kinase 1/2 Inhibitors

Abstract: The impact of JAK1/2 inhibitor therapy prior to allogeneic hematopoietic cell transplantation (HCT) has not been studied in a large cohort in myelofibrosis (MF). In this retrospective multicenter study, we analyzed outcomes of patients who underwent HCT for MF with prior exposure to JAK1/2 inhibitors. One hundred consecutive patients from participating centers were analyzed, and based on clinical status and response to JAK1/2 inhibitors at the time of HCT, patients were stratified into five groups: (a) clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
4
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 39 publications
2
121
4
12
Order By: Relevance
“…157,158 Although the timing of allo-HCT in patients receiving ruxolitinib is not known with certainty, retrospective studies suggest that prior ruxolitinib therapy does not compromise allo-HCT outcomes and that the drug should be continued almost up until the time of conditioning. 159 A plethora of other targeted agents are being studied in MPNs, mostly in MF, both alone and in combination with ruxolitinib. Thus far, some of the combinations have been more promising than others, but in general, both insufficient activity (over that expected with ruxolitinib alone) and additive or overlapping toxicity are of concern.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…157,158 Although the timing of allo-HCT in patients receiving ruxolitinib is not known with certainty, retrospective studies suggest that prior ruxolitinib therapy does not compromise allo-HCT outcomes and that the drug should be continued almost up until the time of conditioning. 159 A plethora of other targeted agents are being studied in MPNs, mostly in MF, both alone and in combination with ruxolitinib. Thus far, some of the combinations have been more promising than others, but in general, both insufficient activity (over that expected with ruxolitinib alone) and additive or overlapping toxicity are of concern.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…In the largest retrospective study so far on the use of JAK 1/2 inhibitors in HCT for MF, 38 higher survival (91% vs 56%) and lower NRM were observed in patients who had clinical improvement on JAK inhibitor therapy at the time of HCT (n 5 23) compared with those who had either stable disease or developed clinical issues such as significant cytopenenias, increasing blasts, or loss of response to JAK inhibitor therapy at HCT. It is not possible to discern whether JAK inhibitor therapy influences HCT outcomes directly through clinical improvement, or indirectly by identifying patients with clinical improvement as those with favorable disease biology.…”
Section: Impact Of Donor Typementioning
confidence: 99%
“…37 However, importantly several studies have found no significant difference in outcomes between MSDs and wellmatched URDs. 17,34,38 The availability of an MSD or well-matched URD may prompt earlier consideration for HCT in a patient. Conversely, HCT may be delayed for patients without an MSD or well-matched URD, and may be more appropriate for patients who have failed nontransplant therapies, are unlikely to do well with JAK 1/2 inhibitor therapy (Table 1), or are at higher risk of LT.…”
Section: Impact Of Donor Typementioning
confidence: 99%
See 1 more Smart Citation
“…Recently Shanavas et al has reported results of large multicenter retrospective study, which tested efficacy of pretransplant JAK1/2 inhibitors therapy [35]. 100 patients with MF who undergo alloHSCT after JAK1/2 inhibitors therapy were included in this study.…”
Section: Clinical Articlesmentioning
confidence: 99%